Effects of resistance training on H+ regulation, buffer capacity, and repeated sprints - Edge, J.; Hill-Haas, S.; Goodman, C.; Bishop, D. (Medicine & Science in Sports & Exercise, 2006)
Purpose: We investigated the effects of resistance training on muscle buffer capacity, H+ regulation, and repeated-sprint ability (RSA).